Effects of different electron acceptors on the methanogenesis of hydrolyzed polyacrylamide biodegradation in anaerobic activated sludge systems. (January 2018) - Zhao, Lanmei; Zhang, Congcong; Bao, Mutai; Lu, Jinren
Graphical abstract: Highlights: HPAM biodegradation was evaluated with SO4 2− and Fe 3+ as electron acceptors. CH4 production was improved with SO4 2− and Fe 3+ as the mixed electron acceptors. Methanobacteriales, Methanomicrobiales and Methanosarcinales were dominant. The thermodynamic opportunity windows of methane-producing were drawn. Acetoclastic methanogenesis was dominant and hydrogenotrophic type was inhibited. Abstract: The type of electron acceptor was a crucial factor in regulating the methanogenic process of anaerobic hydrolyzed polyacrylamide (HPAM) degradation. The combined methods of biodegradation experiments and thermodynamic calculations were applied to explore the effects of different electron acceptors on methanogenic HPAM degradation. Under the conditions of without electron acceptor, SO4 2−, Fe 3+, SO4 2− and Fe 3+ as electron acceptors, HPAM biodegradation ratio reached 31.56%, 41.48%, 49.4% and 61.1%, acetate production reached 0.0532, 28.28, 112.7 and 141.95 mg·L −1, CH4 production reached 0.024, 0.3015, 9.446 and 11.78 mg·L −1, respectively. The synergistic effect of SO4 2− and Fe 3+ further promoted methanogenic HPAM biotransformation. Archaeal community analysis revealed that Methanobacteriales, Methanomicrobiales and Methanosarcinales were dominant. Thermodynamic opportunity windows of methanogenesis with Fe 3+ as electron acceptor are 35 times larger than that with SO4 2− as electron acceptor. It indicated that acetoclastic methanogenesis was dominant and hydrogenotrophic methanogenesis was inhibited in the methane-producing process of anaerobic HPAM degradation.